Partially policy hidden CP-ABE supporting dynamic policy updating - Zuo-bin YING; Jian-feng MA; Jiang-tao CUI (Tongxin xuebao)
Ciphertext-policy attribute-based encryption (CP-ABE) was considered to be appropriate for cloud storage.However,under traditional CP-ABE scheme which was limited in terms of the scale of the data and the quantities of the attributes,computation and communication costs would be introduced correspondingly whenever the data owner wants to update the policy.Moreover,the policy which was stored in the form of plaintext would also result in privacy leakage.Aiming at tackling the above two problems,a novel scheme called partially policy hidden CP-ABE supporting dynamic policy updating (DPUPH-CP-ABE) was proposed.Through utilizing proposed scheme,the computation cost will be reduced,especially on user side,leaving the most computational work to the cloud server.Meanwhile,the value of the user’s attributes will never be revealed to any third parties,and the users’ privacy will be effectively preserved.Besides,the scheme is proved to be adaptively chosen plaintext attack (CPA) secure in the standard model and can support any types of policy updating.